1989
DOI: 10.1097/00000658-198903000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Duodenum-Preserving Resection of the Head of the Pancreas in Severe Chronic Pancreatitis

Abstract: In 128 patients with severe chronic pancreatitis and inflammatory enlargement of the head of the pancreas, a duodenum-preserving resection of the pancreatic head was performed. Median post-operative hospitalization was 15.5 days, and the frequency of reoperation was 5.5%. One patient died during the early post-operative phase, and hospital mortality amounted to 0.8%. After a median follow-up period of 3.6 years (range of 7 months to 16 years), six of 127 patients died (late mortality of 4.7%). Seventy-seven pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
291
1
33

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(329 citation statements)
references
References 14 publications
2
291
1
33
Order By: Relevance
“…It is, however, important to note that this study has evaluated only the immediate consequences of a partial pancreatectomy and that the long-term results of this intervention may be different. In line with this, previous studies in healthy humans who donated 50% of their pancreas to relatives with type 1 diabetes have revealed an increased risk of diabetes in the donors [10,40,41], and previous long-term follow-up studies in patients with chronic pancreatitis have alluded to a progressive increase in the incidence of diabetes subsequent to a partial pancreatectomy [16,[42][43][44]. The present studies have also identified high pre-operative BMI and fasting glucose levels as risk factors for post-operative deteriorations in glucose control.…”
Section: Discussionsupporting
confidence: 54%
“…It is, however, important to note that this study has evaluated only the immediate consequences of a partial pancreatectomy and that the long-term results of this intervention may be different. In line with this, previous studies in healthy humans who donated 50% of their pancreas to relatives with type 1 diabetes have revealed an increased risk of diabetes in the donors [10,40,41], and previous long-term follow-up studies in patients with chronic pancreatitis have alluded to a progressive increase in the incidence of diabetes subsequent to a partial pancreatectomy [16,[42][43][44]. The present studies have also identified high pre-operative BMI and fasting glucose levels as risk factors for post-operative deteriorations in glucose control.…”
Section: Discussionsupporting
confidence: 54%
“…Pancreatic resections encompass various operations including distal pancreatectomy, Whipple 21 , Puestow 22 , Frey 23 and Beger 24 procedures, and TP performed with or without IAT. Although current evidence shows that long-term pain-related outcomes are independent of the type of surgical procedure 25 , up to 40 per cent of patients require opioid analgesia within 12 months following TP 14 and all invariably develop diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several attempts have been made to evaluate the degree of pain in CP using different pain scales and protocols (e.g., a visual analogue scale) [28,29]. However, it is difficult to accurately evaluate pain intensity since the individual perception of pain varies among patients.…”
Section: Discussionmentioning
confidence: 99%